(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This article is devoted to the typology of dictionaries, it presents the scientific conclusions of the great Uzbek and German lexicographers, and analyzes the existing dictionaries created with the participation of the German and Uzbek languages based on them. At the same time, it serves to increase the knowledge of the dictionaries involving orthographic, orthoepic, anthroponomic, toponymic, synonymic, frequency, dialectological, historical, international words, inverse and etymological in these languages, where no research has been done.